Pemanfaatan Bakteri Ureolitik Pada Beton Mutu Tinggi Untuk Menutup Keretakan Akibat Kuat Tekan - M. Nuril Khair; Teuku Budi Aulia; Yunita Idris (Jurnal Permukiman, 2024)
High quality concrete is the primary choice for handling compressive loads in complex building structures such as tall buildings, bridges, dams, and ports. High pressure on high-quality concrete can lead to brittleness and cracking. One solution to improve cracking is by adding bacteria that can produce minerals through microbial processes. This research utilizes ureolytic bacteria, namely the genus Staphylococcus (BSC), Bacillus (BB), and Solibacillus (BBB). Each genus of bacteria was tested with variations of 0.5%, 0.6%, and 0.7%, with 5 test specimens for each variation and 3 control specimens, totaling 48 test specimens. After treatment for 7 days, the test specimens were subjected to a load to induce cracking of 26 MPa. After the cracks formed, observations of calcite growth were made for 7 consecutive days over 28 days. The highest average compressive strength of concrete was found in the BB variation (0.6%). The best calcite growth occurred at the 0.6% variation for Solibacillus genus (BBB1), the 0.6% and 0.5% variations for Bacillus genus (BB1), and the 0.5% variation for Staphylococcus genus (BSC1). FTIR analysis indicates that the test specimens with Bacillus bacteria at the 0.6% variation (BB1) and Solibacillus at the 0.6% variation (BBB1) exhibited high infrared light absorption, while the test specimens with Staphylococcus at the 0.5% variation (BSC1) showed lower light absorption. This demonstrates the better performance of those samplesTop of Form.